2020
DOI: 10.1017/s003329172000135x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between childhood trauma and perceived stress in the general population: a network perspective

Abstract: Background Experiences of childhood trauma (CT) are associated with increased psychological vulnerability. Past research suggests that CT might alter stress processing with a subsequent negative impact on mental health. However, it is currently unclear how different domains of CT exert effects on specific subjective experiences of stress during adulthood. Methods In the present study, we used network analysis to explore the complex interplay between distinct domains of CT and perceived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…Consistent with past work (e.g. Betz et al, 2020;Mundy et al, 2015), we showed independent and direct positive relationships between childhood adversity and both perceived life stress and anxiety symptoms. In addition, and in keeping with our primary hypotheses, we report for the first time a mediating role of two separate indices of anxiety on the relationship between childhood adversity and perceived life stress.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with past work (e.g. Betz et al, 2020;Mundy et al, 2015), we showed independent and direct positive relationships between childhood adversity and both perceived life stress and anxiety symptoms. In addition, and in keeping with our primary hypotheses, we report for the first time a mediating role of two separate indices of anxiety on the relationship between childhood adversity and perceived life stress.…”
Section: Discussionsupporting
confidence: 88%
“…As such, individuals also report stronger negative associations between perceived current life stress and past-year major life events (Back et al, 2008;McLaughlin et al, 2010). Moreover, recent work from Betz et al (2020) identified perceived lack of control in stressful situations as a learned outcome of childhood adversity that becomes generalized to other, less threatening situations and persists into adulthood. Thus, the perceptions of demands imposed by stressful events plays an important role in how an individual will respond, and it is crucial to understand how subjective appraisals of stressful life events are associated with childhood adversity (Cohen et al, 1995;Goldman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly acknowledged that repeated and chronic stress, particularly when exposed to early in life can lead to a sensitization of the psychobiological (stress-)systems ( Lupien et al, 2009 ). This in turn increases the vulnerability and sensitivity to future stress experiences and as such, heightens the probability for future (psycho-)pathology ( McEwen, 1998 ; McLaughlin et al, 2010 ; Betz et al, 2020 ). It is therefore hypothesised that stress will have a differential impact on the two network models due to expected differences in the stress vulnerability of the risk and control groups.…”
Section: Introductionmentioning
confidence: 99%